Analysis Of Work Motivation, Work Discipline And The Environment Work On Employee Performance At Cv. Mal Agri Medan - Lailatul Anjani; Malikhah , Ikhah; Arifin , Daud (Journal of Management, Economic, and Accounting, 2026)
This study aims to analyze Work Motivation, Work Discipline and Physical Work Environment on Employee Performance at CV. Mal Agri Medan. The data analysis technique used is the associative research method with the help of the SPSS version 23 program. This study uses multiple linear regression analysis. The sample in this study was 56 respondents. Primary data collection used a questionnaire. The results of the study indicate that work motivation has a positive and significant partial effect on employee performance at CV. Mal Agri Medan. Work discipline has a positive and significant partial effect on employee performance at CV. Mal Agri Medan. The work environment does not have a significant partial effect on employee performance at CV. Mal Agri Medan. Work motivation, work discipline and work environment do not have a significant partial effect on employee performance at CV. Mal Agri Medan.